Progress of liquid crystal adaptive optics for applications in ground-based telescopes. Issue 3 (29th April 2020) - Zhang, Xingyun; Cao, Zhaoliang; Mu, Quanquan; Li, Dayu; Peng, Zenghui; Yang, Chengliang; Liu, Yonggang; Xuan, Li
ABSTRACT: Liquid crystal (LC) adaptive optics systems (AOS) can potentially be used in ground-based large aperture telescopes, because of their high spatial resolution, low cost and compact size. However, their disadvantages, such as low energy efficiency and slow response speed, still hinder their application. In this paper, we demonstrate solutions to these problems. With newly synthesized fast nematic LC material and using an overdriving technique, the response time of a LC wavefront corrector was reduced to 0.75 ms. Under an open-loop control scheme, a novel optical system was designed to improve the energy efficiency of LC AOS. With those problems resolved, a LC AOS was built for a 1.23-m telescope. This system has a disturbance rejection bandwidth of 80 Hz, and could fully use the energy of 400–900 nm wavebands. Observation results showed that the diffraction limit resolution imaging of the telescope could be obtained after correction, which indicates that the LC AOS is ready to be used in ground-based telescopes for visible waveband imaging.